Pemikiran Ekonomi Islam dalam Perspektif Filsafat Eksistensialisme - Siti Zayyini Hurun'in (UIN Sunan Gunung Djati Bandung, 2021)
Sharia economics is an activity carried out by humans as the subject of production and distribution. Humans carry out economic activities in themselves as individuals and as part of community groups. When it comes to humans, it meets a philosophical dimension. Existentialism is a form of philosophy that strives to analyze the basic structures of human existence to arrive at an awareness of their existence in essential freedom. Existentialist philosophers have an interest in the problem of concrete life as humans. The discussion of the influence of philosophy on economics is about the problems of logic and moral economy which are the object of philosophical study. Economic logic is at the core of discussions to develop thoughts on the Islamic economic system. As for economic morals related to issues of welfare and justice for all humans. In this research method to be used is a method of library research, theoretical research, systematic literature review, and manuscript study. This research was conducted not to legitimize the economic system but to provide critical considerations so that the economy can achieve prosperity and justice for all humans.